A Fluorous Phosphate for the Effective Extraction of LnIII from Nitrate Media: Comparison with A Conventional Organic Phosphate. Issue 5 (19th September 2021) - Ueda, Yuki; Kikuchi, Kei; Tokunaga, Kohei; Sugita, Tsuyoshi; Aoyagi, Noboru; Tanaka, Kazuya; Okamura, Hiroyuki
ABSTRACT: We compare the extraction and separation performance of a newly developed fluorous extractant, tris(4, 4, 5, 5, 6, 6, 7, 7, 7-nonafluoroheptyl) phosphate (TFP) in a fluorinated diluent perfluorohexane, for trivalent lanthanide ions (Ln III ) with a conventional organic extractant, tri- n -butyl phosphate (TBP) in n -octane. Interestingly, the fluorinated extractant TFP exhibits a superior extraction performance for Ln III than the organic extractant TBP, despite the tendency of hydrocarbon fluorination to reduce the extraction performance. Furthermore, the high separation factors among Ln III by TFP suggest that the separation performance of TFP is superior to that of TBP. We proved the superior extraction and separation performance of TFP by comparing the coordination environment of the extracted TFP and TBP complexes, the fluorous phase, and the organic phase. From a microscopic perspective, luminescence lifetime measurements and extended X-ray absorption fine structure spectroscopy revealed the near coordination environment of Eu III in the extracted complex of the extracting phase. Hydrating water scarcely exists in the Eu III -TFP complex, while the Eu III -TBP complex has at least one hydrating water molecule. On the other hand, from a macroscopic perspective, water and nitrate anion transport into the extracting phase during Eu III extraction are revealing. The large amounts of water and NO3 − anions in the organic phase compared to those in the fluorous phase suggest that the extraction of water and NO3 − anions somehow impairs the extraction of Eu III into the organic phase. Hence, TFP in a fluorinated diluent can be used as an alternative extraction and separation system for Ln III .